Limits, stability and disturbance rejection analysis of voltage control loop strategies for grid forming converters in DC and AC microgrids with high penetration of constant power loads - Navarro-Rodríguez, Ángel; Garcia, Pablo; Cano, J.M.; Sumner, M. (2017)
This paper extensively analyzes the operation limits, system stability and disturbance rejection capability of the voltage control loops used in master-slave AC and DC Microgrids (MGs). Two different control schemes are studied analytically, simulated and experimentally tested, focusing on Constant Power Loads (CPL). Additionally, the use of the virtual capacitance (VC) as a tool for response enhancement is introduced. The study pursues the proper selection of the controllers gains and minimization of capacitance values by considering the dynamic behavior.